2020
DOI: 10.1017/s1751731119002933
|View full text |Cite
|
Sign up to set email alerts
|

Addition of fermented and unfermented grape skin in broilers’ diets: effect on digestion, growth performance, intestinal microbiota and oxidative stability of meat

Abstract: Grape skin is a source of polyphenols with antioxidant and antimicrobial properties. Little information is available regarding its application in animal feeding. The present study investigated the effect of inclusion of fermented (FS) and unfermented (UFS) grape skin at two different doses (30 g/kg, FS30 and UFS30, and 60 g/kg, FS60 and UFS60) and 200 mg/kg vitamin E (α-tocopheryl acetate) in a corn–soybean diet on growth performance, ileal protein digestibility, ileal and excreta total extractable polyphenols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
(53 reference statements)
4
24
0
1
Order By: Relevance
“…Besides, no significant difference arose between these two dietary treatments for MDA values. These results are consistent with previous findings of our laboratory [ 10 , 23 , 24 ] since dietary doses of grape polyphenols ranging from 1.17 to 2.92 g/kg also reduced MDA concentration in chicken stored meat, with no significant difference with respect to the dietary supplementation with vitamin E. Interestingly, despite in the present study grape byproducts treatments contained a similar concentration of grape polyphenols, the meat lipid oxidation was only mitigated with the dietary combination of GS and GK, designed to meet grape pomace composition, whereas the individual inclusion of GS or GK in the diet did not reduce MDA values. As reported before, the combination of GS and GK resulted in the highest content of γ-tocopherol when compared to the other groups.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Besides, no significant difference arose between these two dietary treatments for MDA values. These results are consistent with previous findings of our laboratory [ 10 , 23 , 24 ] since dietary doses of grape polyphenols ranging from 1.17 to 2.92 g/kg also reduced MDA concentration in chicken stored meat, with no significant difference with respect to the dietary supplementation with vitamin E. Interestingly, despite in the present study grape byproducts treatments contained a similar concentration of grape polyphenols, the meat lipid oxidation was only mitigated with the dietary combination of GS and GK, designed to meet grape pomace composition, whereas the individual inclusion of GS or GK in the diet did not reduce MDA values. As reported before, the combination of GS and GK resulted in the highest content of γ-tocopherol when compared to the other groups.…”
Section: Discussionsupporting
confidence: 94%
“…In the excreta, TEP content was also higher for birds fed grape byproducts. These results agree with previous findings also reporting the effect of feeding grape pomace, grape seed extract or grape skin on grape polyphenol digestibility [ 10 , 21 , 23 , 24 , 45 ]. Additionally, in the present study we also observed differences in the digestibility of polyphenols when comparing GS and GK treatments.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations